Social Effectiveness and Human-Wildlife Conflict: Linking the Ecological Effectiveness and Social Acceptability of Livestock Protection Tools - Volski, Lara; McInturff, Alex; Gaynor, Kaitlyn M.; Yovovich, Veronica; Brashares, Justin S. (Frontiers in Conservation Science, 2021)
Human-wildlife interactions are embedded within socio-ecological systems (SES), in which animal behavior and human decision-making reciprocally interact. While a growing body of research addresses specific social and ecological elements of human-wildlife interactions, including conflicts, integrating these approaches is essential for identifying practical and effective solutions. Carnivore predation on livestock can threaten human livelihoods, weaken relationships among stakeholders, and precipitate carnivore declines. As carnivores have received greater protection in recent decades, researchers and managers have sought non-lethal tools to reduce predation and promote coexistence between livestock producers and carnivores. For these tools to be successful, they must effectively deter carnivores, and they must also be adopted by producers. Relatively few studies examine the practical and context-specific effectiveness of non-lethal tools, and even fewer simultaneously consider their social acceptability among producers. To address this gap, we suggest that a tool’s ecological effectiveness and social acceptability be analyzed concurrently to determine its social effectiveness. We thus paired an experimental study of a carnivore predation deterrent called Foxlights® with qualitative interviews of livestock producers in Northern California. We placed camera traps in sheep pastures to measure the response of coyotes (Canis latrans) to experimentally deployed Foxlights and interviewed livestock producers before and after the experiment. Our experiment revealed weak evidence for reducing coyote activity with Foxlights, but interviews revealed that the potential adoption of tools had as much to do with their social acceptability and implementation feasibility as with evidence-based measurements of tool effectiveness. Interviewees viewed Foxlights as potentially effective components of husbandry systems, despite the data suggesting otherwise, demonstrating that scientific reductionism may lag behind producer practices of systems-thinking and that isolated demonstrations of a tool’s ecological effectiveness do not drive tool adoption. Future empirical tests of non-lethal tools should better consider producers’ perspectives and acknowledge that data-based tests of ecological effectiveness alone have a limited place in producer decision-making. Iteratively working with producers can build trust in scientific outputs through the research process itself.